The communication of genetically modified food: status, regulation and lessons - Carrera Castaño, Gerardo (Revista Española de Comunicación en Salud, 2020)
Genetically modified organisms (GMOs) constitute an equivocal concept and differentially defined by legislations and sensitivities that has been present in our lexicon for more than 30 years. With a technological and threatening semantic field, genetic modification and GM food have been adopted in different regions of the world, although the acceptance by consumers and public opinion has been, in general, low. The debate over the safety of this type of food is still open and governed by two predominant positions: the principle of equivalence on the one hand, which gives a greater weight to the product and has been adopted by the United States and the Food and Drugs Administration (FDA), and the precautionary principle on the other hand, which gives more weight to the technology and has been adopted by the European Union and the European Food Safety Authority (EFSA). Today, the scientific community opts for the principle of equivalence but, since this is a complex and multidisciplinary debate, a communication method beyond the Deficit Model and an open and rational debate are required.